Chemical composition of three Malaysian Horsfieldia essential oils. Issue 7 (3rd April 2022) - Salleh, Wan Mohd Nuzul Hakimi Wan; Shakri, Natasa Mohd; Khamis, Shamsul; Setzer, William N.; Nadri, Muhammad Helmi
Abstract: This study aims to assess the chemical compositions of the essential oils from three Horsfieldia species namely H. fulva Warb., H. sucosa Warb. and H. superba Warb., which are found in Malaysia. The essential oils were derived from the samples through hydrodistillation which were then characterised by gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS). Based on the findings, the H. fulva, H. sucosa and H. superba essential oils represented 98.2%, 98.7% and 98.5% of the total oils, respectively. The major component of H. fulva oil was identified to be germacrene D (20.8%), H. sucosa oil mainly contained α-cadinol (17.5%), whereas H. superba oil was rich in δ-cadinene (18.2%). To the best of our knowledge, this is the first study of the composition of the essential oils from these selected Horsfieldia species. Graphical Abstract: